A Review of Challenges in Hydraulic Fracturing Operation - Amer S.A, Al Jabri; Girma, T. Chala* (INTI International University, 2020)
Hydraulic fracturing is a prominent method of enhancing hydrocarbon production. It has been implemented from decades to drain the hindered hydrocarbons from the reservoir to the wellbore efficiently. It was reported that a higher percentage of crude oil could be produced from treated wells with hydraulic fracturing technique, with production augmentation sustaining for 40 days in specific well conditions. The two most common types of hydraulic fracturing extensively used are propped hydraulic fracturing and acid hydraulic fracturing. Both methods incorporate similar intention of creating better fracturing conductivity inside reservoir formation for an enhanced well productivity. The treatment fluid contains additives and materials which could be extracted naturally and should meet the best fluid optimization to overcome various challenges. The technique is sophisticated and requires high level of professionalisms and geological awareness to do such successful well production treatment. This paper is, therefore, aimed at reviewing an expandable view on some of challenges associated with hydraulic fracturing operation which hampered successful stimulation operation. It also highlights different techniques that could be used in alleviating the challenges encountered.